LGBT BİREYLERDE DİNÎ İNANÇ, DİN ve TANRI TASAVVURU, DİNÎ ve MANEVÎ BAŞA ÇIKMA SÜRECİ - (:unkn) unknown (My University, 2014)
Din ve manevîyât (spirituality) hayatın vazgeçilmez unsurlarıdır, hemen hemen her birey dinî ya da manevî bir eğilime sahiptir. LGBT bireyler üzerine yapılan nitel bir araştırmayı içeren bu makale, bu bireylerin dinî ve manevî eğilimlerini konu edinmektedir. Makalede şu sorulara cevap aranmaktadır: Katılımcıların inanç/inançsızlık durumları nedir? Katılımcıların din tasavvuru nasıldır? Katılımcıların Tanrı tasavvuru nasıldır? Katılımcılar hayatın zorluklarıyla başa çıkma sürecinde dinî/manevî unsurları kullanmakta mıdır? Türkiye'de LGBT bireylerle ilgili bazı çalışmalar olmakla birlikte, onların dinî ve manevî eğilimlerine dair herhangi bir çalışma bulunmamaktadır. Bu durum da makalenin literatüre katkısını daha önemli kılmaktadır. Bu araştırmanın örneklemini, İstanbul'un Beyoğlu semtinden seçilen 30 LGBT birey oluşturmaktadır. Örneklem, on bir gey, altı lezbiyen, altı biseksüel ve yedi transeksüel bireyi içermektedir. Katılımcıların %40' kendisini "Müslüman" olarak tanımlarken, %60'ı kendisini "Alevi", "agnostik", "ateist" ve "kararsız" olarak tanımlamıştır. Araştırma bulgularına göre, bireyler kimliklerini kabul ve onu açıklama sürecinde yaşadıkları sıkıntılar da dâhil olmak üzere hayatın zorluklarıyla başa çıkma sürecinde dinî ve manevî unsurlar kullanmışlardır. Katılımcıların "merhametli Tanrı" tasavvuru "cezalandırıcı Tanrı" tasavvuruna göre daha belirgindir.

Religion and spirituality are indispensible elements of life. The most of people have religious or spiritual inclination in their life. The subject of this paper which is conducted qualitative research, the religious and spiritual inclinations of LGBT individuals in the case of Turkish Islamic Culture. This study answers these questions: How do subjects describe themselves concerning believing in God or Religion? How are the representations of God and Religion of the Subject? How do subjects use religious/spiritual motifs in the process of coping with adversities of the life? Although there are several studies on LGBT individuals in Turkey, the religious and spiritual inclinations of these people have not examined enough yet. Therefore this study has a claim on being the first study in this context, and contribution to the literature. Sample of this research were interviewed with thirty people, including six lesbian, eleven gay, six bisexual and seven transgender individuals in Beyoglu district of Istanbul. Findings indicated that LGBT people's level of spirituality is higher than their religiosity level. It is seen that most of them (%40) defined themselves as Muslims. Some others have used "atheist", "Alevi", "agnostic" and "irresolute" concepts for defining their beliefs. It was seen that they received support from religion and spirituality in the process of coping with life adversities even coping with stress of accepting of their sexual orientation and coming out process. Findings also showed that LGBT individuals have inclination to accept merciful God representation instead of punitive God representation.
Religious Belief, Representations of Religion and God, and Religious/Spiritual Coping Process among Lesbian, Gay, Bisexual and Transsexual Individuals
Keywords: Din Bilimi